2021
DOI: 10.1111/aos.15047
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in the fractal dimension of the retinal microvasculature, effects of cardiovascular risk factors and smoking behaviour

Abstract: Purpose: This cross-sectional study investigates the association between retinal vessel complexity and age and studies the effects of cardiovascular health determinants. Methods: Retinal vessel complexity was assessed by calculating the boxcounting fractal dimension (D f ) from digital fundus photographs of 850 subjects (3-97 years). All photographs were labelled as 'non-pathological' by the treating ophthalmologist. Results: Statistical models showed a significantly decreasing relationship between age and D f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
3
4
0
Order By: Relevance
“…Current smoking status was positively correlated with artery fractal dimension, vessel density, and artery and vein average width; was opposite in correlation to the correlation of blood pressure and sleep indices. Nevertheless, these results are consistent with a previous study 7 that reported a positive correlation between fractal dimension and the number of pack-years. A possible explanation is a pathological angiogenic effect, mediated by multiple growth factors, including vascular endothelial growth factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Current smoking status was positively correlated with artery fractal dimension, vessel density, and artery and vein average width; was opposite in correlation to the correlation of blood pressure and sleep indices. Nevertheless, these results are consistent with a previous study 7 that reported a positive correlation between fractal dimension and the number of pack-years. A possible explanation is a pathological angiogenic effect, mediated by multiple growth factors, including vascular endothelial growth factor.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have utilized deep learning from fundus images, in order to directly predict mortality risk 4 and conditions such as hypertension, dyslipidemia, and obesity 3 . Some associations were also found in previous studies between fundus microvascular width, tortuosity, density or fractal dimension and obesity 5 , blood pressure 6 , smoking 7 , sleep apnea 8,9 , and blood glucose 3 .…”
Section: Introductionsupporting
confidence: 76%
“…First, there are likely confounders for which we could not adjust because of a lack of data. For example, smoking is more prevalent among individuals with psychosis and is known to affect retinal vasculature . Second, our case definition of schizophrenia was based on ICD-10 codes from hospital admissions data, which may be prone to misclassification bias.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] These features include arteriole narrowing, branching patterns, and vessel tortuosity. Kirin 44 To assure that age differences were not driving the results we found, we tested our model using both an age matched and non-age matched unrelated cohort. We found that performance improved slightly on the test set after age matching the related and unrelated cohorts.…”
Section: Discussionmentioning
confidence: 99%